Audiencias digitales, recepción de la idea de cine ecuatoriano (Monográficos) - Estrella Silva, Euler Santiago (2022)
The idea of Ecuadorian cinema has been discussed and debated in the cinematographic sectors, where it is agreed that it is not a genre or a univocal concept. But from the viewpoint of audiences and consumers, such an idea is put into crisis. The present reception study focuses on the relationship that digital audiences have with Ecuadorian cinema, their interpretations and the imaginary they create. Despite the emergence of platforms that group together a series of titles from local productions, the subjects consulted were unaware of these spaces. They identify and point to the Ecuadorian cinema as an expression of diversity, of a growth in talent and technical quality, but with recurring themes linked to drama, sadness, social problems, without creativity from the scripts, flaws in the performances and with shortcomings of resources. It is an invisible cinema loaded with prejudices.